Prevalence and clinical characteristics of apparent therapy-resistant hypertension in patients with cardiovascular disease: a cross-sectional cohort study in secondary care - de Beus, Esther (BMJ Open, 2017)
OBJECTIVES: Our aim was to investigate the prevalence of apparent therapy-resistant hypertension (aTRH) in patients with clinical manifest cardiovascular disease (CVD), and to study clinical characteristics related to aTRH in this population. SETTING: The SMART (Second Manifestations of ARTerial disease) study is a large, single-centre cohort study in secondary care. PARTICIPANTS: Office blood pressure (BP) at inclusion was used to evaluate BP control in 6191 hypertensive patients with clinical manifest (cardio)vascular disease. Therapy-resistant hypertension was defined as BP ≥140/90 mm Hg despite use of antihypertensive drugs from ≥3 drug classes including a diuretic or use of ≥4 antihypertensive drugs irrespective of BP. Logistic regression analysis was used to explore the relationship between clinical characteristics measured at baseline and presence of aTRH. RESULTS: The prevalence of aTRH was 9.1% (95% CI 8.4 to 9.8). Prevalence increased with age and when albuminuria was present and was higher in patients with lower estimated glomerular filtration rate (eGFR). Presence of aTRH was related to diabetes, female sex, duration and multiple locations of vascular disease, body mass index and waist circumference. Carotid intima-media thickness was higher (0.99±0.28 vs 0.93±0.28 mm) and ankle-brachial index lower (1.07±0.20 vs 1.10±0.19) in patients with aTRH compared with patients without aTRH. CONCLUSION: aTRH is prevalent in patients with clinical manifest CVD and is related to clinical factors known to be related with increased vascular risk, and with lower eGFR.